A toolbox for miRNA analysis - Svoboda, Petr (FEBS letters, 2015)
MicroRNAs (miRNAs) are small regulatory RNAs, which mediate selective repression of gene expression. miRNAs play important roles in many natural and pathological processes. Numerous tools were developed for their detection and functional analysis. There are many excellent articles covering different areas of miRNA biology in detail. At the same time, I think there are many colleagues who face a miRNA-related research problem and would appreciate having an introductory general overview of tools for miRNA analysis, which would help them in considering available options. Accordingly, this review provides an elementary roadmap to navigate among available tools for miRNA analysis. The most common problems and errors observed in miRNA research are also discussed.
Keywords: Reporter; Animals; Inhibition; MicroRNA; MicroRNAs; Antagomir; lidé; zvířata; mikro RNA; Locked nucleic acids; Humans